2019
DOI: 10.1016/j.eucr.2019.100881
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of renal gastrointestinal stromal tumor

Abstract: Renal cell carcinoma (RCC) accounts for about 3% of adult cancers. RCC is the third most common cancer among the urogenital cancers, clear-cell RCC being the most common histological subtype. Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract and are derived from interstitial Cajal cells (ICCs). The ICCs in the urinary system were first shown in 2003 in a study by Solari et al. However, there is no publication of a GIST of renal origin yet. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This was the first case of EGIST originating from the pericardium. Reports of EGIST presenting in the kidney, adrenal gland, inferior vena cava, vagina, and scrotum have been found [9][10][11][12][13]. Diagnosis can often be delayed due to small tumor size and lack of clinical symptoms in the tumor's early stages [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…This was the first case of EGIST originating from the pericardium. Reports of EGIST presenting in the kidney, adrenal gland, inferior vena cava, vagina, and scrotum have been found [9][10][11][12][13]. Diagnosis can often be delayed due to small tumor size and lack of clinical symptoms in the tumor's early stages [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the association between GIST and second primary malignancies. Next to other gastrointestinal tumors, genitourinary cancer is associated with GIST [2][3][4][5][6]. In many cases, the association is related to KIT mutations [7,8].…”
Section: Introductionmentioning
confidence: 99%